Transcriptome and metabolome profiling reveal the regulatory mechanism of protein accumulation in inferior grains of indica-japonica rice hybrids - Xincheng Zhang (Elsevier, 2021)
Protein content in the inferior grains (IG) has a great impact on eating quality of indica-japonica rice hybrids. However, the mechanisms of the difference in protein accumulation between IG and superior grains (SG) remains unclear. A field experiment was carried out using an indica-japonica hybrid Yongyou17 and two nitrogen levels. The result showed that prolamin concentration was significantly higher in IG than SG, while there was no significant difference in glutelin concentration between the two types of grains. Totally, 465 metabolites were identified, and 26 “core metabolites” differentially accumulated in IG could be divided into three types. Asparagine and 1-aminocyclopropanecarboxylic acid were markedly increased in IG, while flavonoid compounds were obviously reduced, in comparison with those in SG. Weighted gene co-expression network analysis indicated that bisque4 and darkorange2 modules for type 1 and type 3 of the “core metabolites” were closely associated with the synthesis of ribosomal protein and stress response, respectively. Eight hub genes, i.e. rpL32_8.1, novel.907, RPS15a and RPL13a.4 in bisque4 and OsSAP5, OsHSP20, PRX12 and DUF3741 were identified in darkorange2. In addition, genes WDR, R2R3-MYB and bHLHs were significantly down-regulated in IG, companied by reduced synthesis of flavonoid compounds. IG had higher ethylene and N levels, resulting more protein accumulation. The current study provides a new insight into the regulation network of protein synthesis in IG of indica-japonica rice hybrids.